Signos de Leser-trélat en un carcinoma de células en anillo de sello - Catarina Teles Neto; Marta Valentim (Sociedade Galega de Medicina Interna, 2022)
80 year-old man presenting with weight loss, right hypochondrium pain and vomiting, with 1 year of symptoms evolution, was admitted. Physical exam showed multiple hyperkeratotic lesions, distribuing on trunk and dorsal region, a paraneoplasic sign knowing as Leser-Trélat sign. Multiple nodular hepatic hypoechogenic formations were detected on the echography. Analytically: CEA 2627 ng/mL. CT body scan: lymphatic, pulmonary, suprarenal and hepatic metastasis, without evidence of the primary tumor. Upper Endoscopy and Colonoscopy were performed, without alterations. The Hepatic biopsy revealed: infiltration by well differentiated carcinoma, with mucus lakes and numerous signet-ring cells, whose immunohistochemical profile was compatible with origin in the gastrointestinal tract.